Role of NaF on the performances of β-hemihydrate gypsum plaster. (1st September 2022) - Jia, Ruiquan; Fan, Yufeng; Wang, Qiang; Xue, Junfeng
Abstract: Phosphogypsum can be used to prepare β-hemihydrate gypsum (β-CaSO4 ·1/2H2 O) plaster. A prerequisite for any effective reuse of phosphogypsum is to understanded the act by which impurities in phosphogypsum influence the performance of β-CaSO4 ·1/2H2 O plaster, and the role NaF was explored in this study. The results indicate that during β-CaSO4 ·1/2H2 O hydration, the percentage of free F decreased considerably owing to its adsorption and the rapid precipitation of CaF2, and the percentage of free Na was very higher due to its strong solvation. NaF enhanced β-CaSO4 ·1/2H2 O dissolution and CaSO4 ·2H2 O precipitation, which included two pathways involving Ca 2+ and SO4 2− as well as [CaSO4 ] 0 . The acceleration of NaF can be ascribed to the nucleation of CaF2 whose acceleration was slight and the catalysis of Na  +  whose acceleration was remarkable due to the transformation from [NaSO4 ] - to [CaSO4 ] 0 . The evolution of the zeta potential was one of the reasons for the faster initial setting at the lower hydration degree. The lower bonding force among the crystal grains of CaSO4 ·2H2 O, the coarsened CaSO4 ·2H2 O crystal grains and the quick hydration rate all contributed to the drop in 2-h and dry strengths, and when the dosage of NaF was 0.5%, the dry strength increased due to the optimized morphology of CaSO4 ·2H2 O crystal grains. The dosage of NaF should be limited to ≤1.0% to avoid excessive strength loss. Highlights: NaF greatly accelerated β-CaSO4 ·1/2H2 O hydration at low dosage (0.5%). The acceleration of NaF was due to the nucleation of CaF2 and the catalysis of Na + . The catalysis of Na + was due to the transformation from [NaSO4 ] - to [CaSO4 ] 0 . Besides the formation of CaF2, a certain amount of F − was adsorbed by solids. NaF accelerated setting by decreasing zeta potential and degree of hydration.